47 The importance of constructive alignment in designing simulation-based education. (17th November 2016) - Blanks, Thomas; Baxendale, B; Woodier, N; Ravindra, P
Abstract : The Joint Committee on Surgical Training has made specific reference to the role of simulation-based training to enhance surgical training; both with mention of technical and non-technical skills. The Urology Specialist training programme has been one of the front runners in adopting this approach. As with all Collegiate level curriculum changes these need effective mapping to local needs; in this case the pilot programme featured a strong clinical aspect that focussed on the technical management of urological based medicine. This was a specific educational strategy co-designed with the lead surgical trainee. Unfortunately the emphasis on clinical management was not meet with enthusiasm by the pilot group who felt that some scenarios had little relevance to Urology trainees. There were also significant levels of anxiety with regards to the day itself which may have impacted on engagement. The general comments were strongly weighted towards a belief that the programme would be more effective by moving away from clinical skills and towards a focus on non-technical skills. This was of significant interest as feedback from more junior trainees often highlights the desire to strengthen technical skills being more highly ranked in their agenda for professional development. This may be a result of the higher specialist trainees being more comfortable in their clinical management and therefore looking to other avenues for development. This evaluation has significant influenced the redesign of the programme prior to formal implementation. In conjunction with surgical colleagues the programme now has a far more non-technical focus on professional capabilities as per the GMC guidance. This attempts to address some of the concerns of the candidates regarding the mix between technical and non-technical focus. This aims to put the candidates into novel scenarios that require clear development of these professional capabilities so crucial to modern medical practice.